2019
DOI: 10.1353/asr.2019.0012
|View full text |Cite
|
Sign up to set email alerts
|

Author Meets Critics: Comparative Advertising: History, Theory, and Practice

Abstract: This Author Meets Critics conversation focuses on Fred Beard's book Comparative Advertising: History, Theory, and Practice (Lexington Books, 2018). Beard meets with three advertising scholars and a leading creative executive to discuss the following topics: comparative advertising types, the history of comparative advertising, comparative advertising's effectiveness, the regulation of comparative advertising in politics, comparative advertising and social media, consumer responses to social media, changing def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…According to Beard (2018), comparative advertising is appropriate in this specific case: SBs vs NBs. It is the correct approach when the competition is intensifying in static or slow-growth markets characterized by two or more “me-too” competitors and that a corresponding need for brand differentiation arises.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Beard (2018), comparative advertising is appropriate in this specific case: SBs vs NBs. It is the correct approach when the competition is intensifying in static or slow-growth markets characterized by two or more “me-too” competitors and that a corresponding need for brand differentiation arises.…”
Section: Introductionmentioning
confidence: 99%
“…Such ads could therefore develop in the coming years because SBs are major competitors of NBs. However, previous research on comparative advertising has examined NBs exclusively (Dianoux et al , 2013; Beard, 2018). Comparisons between SBs and NBs are thus lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Fascinating interactions between ad type and gender were found. The literature of comparative advertising overlooked this area of demographic effects and gender effects in particular (Beard, 2018). In the absence of studies, knowledge based on Chang (2007) suggested that women are more likely to detect manipulative intent and practitioners highlighted a potential greater empathy towards the attacked brand among females.…”
Section: Discussionmentioning
confidence: 99%
“…Manzur, et al (2012) reported a greater message believability for ICA relative to DCA in Chile, while Jeon and Beatty (2002) found a systematic positive consumer response to DCA over ICA in Korea and no difference in response for the USA. There is research supporting the relative effectiveness of DCA over ICA in the USA and the UK (Beard, 2018;Petrovici, et al, 2016).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation